Efektivitas Model Pembelajaran Kooperatif Tipe Example Non Example Untuk Meningkatkan Hasil Belajar IPA Pada Siswa Kelas V dI MI Al Hasanah Canggu Badung - Hayati, Nurul; Robihat, Robihat; Nurkholis, Nurkholis (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This research was conducted because teachers in conducting learning still pay less attention to students' thinking abilities and the use of learning models is still not varied so that students' learning motivation is difficult to grow so that the learning outcomes obtained by students still do not reach the KKM value. Therefore, this research was conducted to find out how the effectiveness of the cooperative learning model type example non example in improving student learning outcomes about Digestive Organs in Humans and Animals As the subject of research here are students of class V (five) totaling 24 students consisting of 13 boys and 11 girls. The research procedure carried out in the form of planning, implementation of actions, observation, evaluation, reflection which is recycled (cycle). After conducting the research, the results of the improvement were obtained in increasing students' mastery of the learning material, which before the application of the example non example cooperative learning model or during the pre-cycle the average student score was 60.29 and after the research was carried out it increased to 75.83 in cycle 1 and increased again in cycle 2 to 82.91 so that it can be concluded that the application of the Example Non Example cooperative learning model can effectively improve student learning outcomes about Human and Animal Digestive Organs in science subjects in Class V (five).